2013
DOI: 10.1128/jcm.02710-12
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin Morbillivirus Infection in a Captive Harbor Seal (Phoca vitulina)

Abstract: CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…In addition, this is not the first description of DMV in the Mediterranean Sea in 2011. In Italy, DMV has been reported in striped dolphins, bottlenose dolphins and fin whales on almost the same dates as this report [21-24]. Accordingly, Morbillivirus infection finding might be related with the rise in strandings in 2011.…”
Section: Case Presentationsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, this is not the first description of DMV in the Mediterranean Sea in 2011. In Italy, DMV has been reported in striped dolphins, bottlenose dolphins and fin whales on almost the same dates as this report [21-24]. Accordingly, Morbillivirus infection finding might be related with the rise in strandings in 2011.…”
Section: Case Presentationsupporting
confidence: 75%
“…Complementarily, the N2 fragment of 495 bp [19] and the N1 fragment of 181 bp of the nucleoprotein gene [5] were compared with other DMV nucleoprotein gene sequences, which confirmed that the 2011 DMV strain evolved from the 1990 DMV strain and the 2007 DMV strain (Figure 3). The N1 sequence was 100% identical to the others observed in the Mediterranean Sea from 2007 to 2012 [20,21], whereas the N2 fragment showed a similarity of 99.8% with the DMV sequence obtained from the Globicephala melas mass stranding of 2007 [20]. …”
Section: Case Presentationmentioning
confidence: 59%
“…1,3 This finding argues in favor of prolonged DMV circulation in the Western Mediterranean and simultaneously supports the hypothesis stating that an inadequate level of anti-viral immunity exists in the striped dolphins that inhabit this area. Based on the available data, it can be predicted that cyclic DMV epidemics should be occurring every 3–5 years in the Western Mediterranean.…”
supporting
confidence: 78%
“…It is likely these were spillover events and it is thus reasonable to propose the virus is maintained in other marine mammal species during the intervening period. For example interspecies transmission of CeMV from a dolphin to a captive seal has been demonstrated [62]. Atlantic harp seal populations exceed 7 million which is well in excess of the numbers to maintain endemic transmission of a morbillivirus.…”
Section: Where Did Morbilliviruses Come From?mentioning
confidence: 99%